High Risk of Influenza Virus Infection Among Swine Workers: Examining a Dynamic Cohort in China. (1st September 2019) - Borkenhagen, Laura K; Wang, Guo-Lin; Simmons, Ryan A; Bi, Zhen-Qiang; Lu, Bing; Wang, Xian-Jun; Wang, Chuang-Xin; Chen, Shan-Hui; Song, Shao-Xia; Li, Min; Zhao, Teng; Wu, Meng-Na; et al.
Abstract: Background: China is thought to be a hotspot for zoonotic influenza virus emergence, yet there have been few prospective studies examining the occupational risks of such infections. Methods: We present the first 2 years of data collected from a 5-year, prospective, cohort study of swine-exposed and -unexposed participants at 6 swine farms in China. We conducted serological and virological surveillance to examine evidence for swine influenza A virus infection in humans. Results: Of the 658 participants (521 swine-exposed and 137 swine-unexposed), 207 (31.5%) seroconverted against at least 1 swine influenza virus subtype (swine H1N1 or H3N2). Swine-exposed participants' microneutralization titers, especially those enrolled at confined animal feeding operations (CAFOs), were higher against the swine H1N1 virus than were other participants at 12 and 24 months. Despite elevated titers, among the 187 study subjects for whom we had complete follow-up, participants working at swine CAFOs had significantly greater odds of seroconverting against both the swine H1N1 (odds ratio [OR] 19.16, 95% confidence interval [CI] 3.55–358.65) and swine H3N2 (OR 2.97, 95% CI 1.16–8.01) viruses, compared to unexposed and non-CAFO swine workers with less intense swine exposure. Conclusions: While some of the observed increased risk against swine viruses may have been explained by exposure to human influenza strains, study data suggest that even with elevated preexisting antibodies, swine-exposed workers were at high risk of infection with enzootic swine influenza A viruses. Abstract : A 2-year (2015–2017) prospective cohort study of 187 swine workers in China revealed that swine workers were at increased risk of infection with the endemic swine influenza A viruses, despite having preexisting elevated neutralizing antibodies against these viruses.